2013
DOI: 10.1152/ajpregu.00180.2013
|View full text |Cite
|
Sign up to set email alerts
|

Selective leptin resistance revisited

Abstract: In addition to effects on appetite and metabolism, leptin influences many neuroendocrine and physiological systems, including the sympathetic nervous system. Building on my Carl Ludwig Lecture of the American Physiological Society, I review the sympathetic and cardiovascular actions of leptin. The review focuses on a critical analysis of the concept of selective leptin resistance (SLR) and the role of leptin in the pathogenesis of obesity-induced hypertension in both experimental animals and humans. We introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
127
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 167 publications
1
127
2
6
Order By: Relevance
“…Leptin sensitivity for cardiovascular actions during aging, however, is unknown. It is possible to observe divergent effects in this regard as previous studies have shown that resistance is selective to the metabolic, but not cardiovascular, actions of leptin in obese animal models perhaps due to brain-and signaling pathway-specific mechanisms (28). Interestingly, the leptin injection did produce a transient decrease in blood pressure in older rats suggesting at least some responsiveness in cardiovascular pathways in the dorsal medulla during aging.…”
Section: Discussionmentioning
confidence: 97%
“…Leptin sensitivity for cardiovascular actions during aging, however, is unknown. It is possible to observe divergent effects in this regard as previous studies have shown that resistance is selective to the metabolic, but not cardiovascular, actions of leptin in obese animal models perhaps due to brain-and signaling pathway-specific mechanisms (28). Interestingly, the leptin injection did produce a transient decrease in blood pressure in older rats suggesting at least some responsiveness in cardiovascular pathways in the dorsal medulla during aging.…”
Section: Discussionmentioning
confidence: 97%
“…18,19 In the case of leptin, however, prevailing evidence suggests that the opposite is also true, namely that leptin may trigger central and peripheral sympathoexcitation. 38,39 This possibility has been recently strengthened by the results of a microneurographic study showing that in healthy normoweight subjects acute infusion of leptin triggers a significant increase in MSNA. 40 It is thus conceivable to conclude that the sympathoinhibitory effects of sleeve gastrectomy are mediated, at least in part, by the reduction in the elevated levels of plasma leptin, which activate the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been suggested that this resistance is selective, whereby the cardiovascular effects of leptin remain intact, while the metabolic effects of leptin are abolished (26). Current research on the mechanisms underlying selective leptin resistance (SLR) focuses on deficits in leptin signaling.…”
Section: Discussionmentioning
confidence: 99%